(untitled) (Indian Journal of Public Health Research & Development, 2020)
Objects: to identify effectiveness of oral cryotherapy on prevention from mucositis in cancer patients under chemotherapy. Methods: the study used quasi experimental method with pre-post test with control group. The samples were 32 patients for intervention group and control group, taken by using consecutive sampling technique. Mucositis was measured by using questionnaires on Oral Assessment Guide (OAG) while the data analyzed by Wilcoxon test and Mann Whitney test. Results: The result showed, in the post intervention in the intervention group, 24 respondents were not affected by mucositis at p-value=0.008 (p<0.05); in the post-intervention in both groups, there were difference in the value of mucositis measured by OAG at p-value=0.003 (p<0.05). Conclusion: Oral Cryotherapy could prevent mucositis in cancer patients who were under chemotherapy.